The Effectiveness of Mobile-Based Mental Health App on Anxiety and Cognitive Distortions - Darbani, Seyed Ali; Mirseify fard, Leila Sadat (Journal of Personality and Psychosomatic Research (JPPR), 2025)
This study aimed to evaluate the effectiveness of a mobile-based mental health application in reducing anxiety symptoms and cognitive distortions among young adult users. A randomized controlled trial was conducted with 30 participants (15 in the experimental group and 15 in the control group) recruited from Iran. The intervention consisted of a mobile application delivering 12 CBT-based sessions over six weeks. Standardized tools—the Beck Anxiety Inventory (BAI) and the Cognitive Distortions Scale (CDS)—were used to assess outcomes at pre-test, post-test, and five-month follow-up. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests via SPSS-27. The repeated measures ANOVA revealed significant main effects of time (F = 44.52, p < .001, η² = .614 for anxiety; F = 39.73, p < .001, η² = .595 for cognitive distortions), group (F = 35.45, p < .001 for anxiety; F = 41.68, p < .001 for cognitive distortions), and time × group interactions (F = 42.53, p < .001 for anxiety; F = 37.21, p < .001 for cognitive distortions). Bonferroni post-hoc tests confirmed that the experimental group experienced significant reductions in both anxiety and cognitive distortions from pre-test to post-test (p < .001) and from pre-test to follow-up (p < .001), with no significant relapse over time (p > .05). The findings support the effectiveness of a structured mobile-based mental health application in reducing anxiety and maladaptive thinking patterns. The sustained improvements at five-month follow-up suggest that such digital interventions can offer accessible and durable mental health support.